Democratic Socialism in Britain and Sweden - Hamilton, Malcolm B. author. aut Link
XIII, 270 p.
Keywords: A study of the fluctuations in the degree of radicalism and socialism in the domestic policies of Socialist, Social Democratic and Labour parties in Western industrial democracies, examining the influence of votes secured in elections and the aim of unity within the party and with the unions.